1996
DOI: 10.1002/(sici)1097-0142(19961101)78:9<1942::aid-cncr15>3.0.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of proliferation markers and their prognostic value for women with endometrial carcinoma: Ki-67, proliferating cell nuclear antigen, and flow cytometric S-phase fraction

Abstract: BACKGROUND.The understanding of proliferation is a central issue in oncology. Sev-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 36 publications
1
15
2
Order By: Relevance
“…This finding is not new. [15][16][17][18][19][20][21] However, the strength of our prospective study is that this is the first that presents 10-year results of flow cytometric DNA analysis from fresh tumor samples. In fact, it is known that histograms from paraffin-embedded material are less accurate than those from fresh tissue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not new. [15][16][17][18][19][20][21] However, the strength of our prospective study is that this is the first that presents 10-year results of flow cytometric DNA analysis from fresh tumor samples. In fact, it is known that histograms from paraffin-embedded material are less accurate than those from fresh tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to improve the outcome of patients with endometrial cancer a new, more accurate prognostic assessment is mandatory to identify patients with high-risk disease. In recent years research focused on biological aspects of the tumor, such as DNA content, [8][9][10][11][12][13][14][15][16][17][18][19][20][21] protooncogenes, [22][23][24] and tumor-suppressor genes expression [25][26][27][28][29][30][31][32][33] that have been investigated as possible predictors of clinical outcome in endometrial cancer. The advantage of these parameters is that they are considered to provide objective and reproducible information.…”
mentioning
confidence: 99%
“…Geisler et al (37), in an earlier study on a series of 39 patients, had shown MIB-1 to be indicator of increased risk of recurrence. Nordstrom et al (38) found MIB-1/Ki-67 expression and S-phase fraction were significantly related to disease-specific survival in patients with endometrial carcinoma. Despite the methodological differences between these studies, all found MIB-1 to be an independent prognostic indicator of survival.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of the mutation of PTEN remains controversial, since this has been found to be positively associated with prognosis, whereas the loss of expression and methylation of PTEN are negatively associated with prognosis (54). A high proliferative activity of tumor cells based on Ki-67 expression and the number of mitoses is associated with a poor prognosis in endometrial cancer; however, the multivariate survival analyses do not show concordant results, which may be due to technical differences in measuring Ki-67 (55,56). The loss of expression of Bcl-2 and the resultant reduced apoptosis are also associated with a poor prognosis (39).…”
Section: Biomarkers For Prognosis and Treatmentmentioning
confidence: 99%